2017
DOI: 10.1038/srep45995
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfides (H2Sn) produced from the interaction of hydrogen sulfide (H2S) and nitric oxide (NO) activate TRPA1 channels

Abstract: Hydrogen sulfide (H2S) exerts synergistic effects with another gaseous signaling molecule nitric oxide (NO) on ion channels and vasculature. However, the mechanism of the synergy is not well understood. Here, we show that the interaction between H2S and NO generates polysulfides (H2Sn), which activate transient receptor potential ankyrin 1 (TRPA1) channels. High performance liquid chromatography with tandem mass spectrometry analysis, along with the imaging of intracellular Ca2+ and H2Sn, showed that H2Sn and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 41 publications
(75 reference statements)
2
93
0
Order By: Relevance
“…Thus HSNO can act a signaling molecule that may play a key role in cellular redox regulation [138]. Emerging data shows that the interaction between H 2 S and NO can also generate polysulfides (H 2 S n ; H 2 S 2 and H 2 S 3 ) [139]. In this study it was shown that H 2 S n generation was a fast reaction, and it activated transient receptor potential ankyrin 1 (TRPA1) channels in astrocytes and dorsal root ganglion (DRG) neurons, which can modify synaptic activity [140, 141].…”
Section: Interaction Between No and H2smentioning
confidence: 99%
See 1 more Smart Citation
“…Thus HSNO can act a signaling molecule that may play a key role in cellular redox regulation [138]. Emerging data shows that the interaction between H 2 S and NO can also generate polysulfides (H 2 S n ; H 2 S 2 and H 2 S 3 ) [139]. In this study it was shown that H 2 S n generation was a fast reaction, and it activated transient receptor potential ankyrin 1 (TRPA1) channels in astrocytes and dorsal root ganglion (DRG) neurons, which can modify synaptic activity [140, 141].…”
Section: Interaction Between No and H2smentioning
confidence: 99%
“…H 2 S activates eNOS by an Akt-dependent phosphorylation of the protein [132]. NO can interact with H 2 S to form HSNO [138] and H 2 S n [139]; H 2 S can interact with NO 2 − [124] or with RSNO [147, 148] to produce NO. H 2 S decreases the sensitivity of the cGMP pathways and also it modifies K Ca channels to decrease their sensitivity to NO.…”
Section: Figurementioning
confidence: 99%
“…Many antihypertensive drugs exert their protective effects at least in part by increasing NO bioavailability [15]. Deficiencies in H 2 S/NO may contribute to the development of hypertension, and in this context, combination therapy may prove fruitful in managing hypertension [8, 89, 243, 305]. …”
Section: Discussionmentioning
confidence: 99%
“…HSNO acid could freely diffuse through the membranes, acting as an NO carrier [244, 246]. HSNO acid could also react with hydrogen persulfide (HSSH) to produce SSNO − , which also can act as a NO carrier, leading to relaxation of VSM cells upon NO release [220, 243, 244]. In addition, HSNO is relatively unstable and in the presence of H 2 S and HSSH can produce nitroxyl (HNO) [220, 243, 244], which exerts vasorelaxatory effects by activation of cGMP-dependent [247] and independent [248] pathways.…”
Section: Interaction Between H2s and Nomentioning
confidence: 99%
“…H 2 S plays synergistically with NO to form polysulfides (H 2 S n ) to act as TRPA1 channel activator in vasodilation [30]. Meanwhile, ZYZ-803, a slow-releasing H 2 S-NO hybrid molecule, could exert vasorelaxant effect [31] and angiogenesis [32] activity better than S-Propargyl-Cysteine (SPRC) and furoxan alone or together.…”
Section: Physiological Effects Of H2s and Related Molecular Mechanismmentioning
confidence: 99%